Chronic hepatosplenomegaly in African school children: a common but neglected morbidity associated with schistosomiasis and malaria. - Shona Wilson; Birgitte J Vennervald; David W Dunne (Public Library of Science (PLoS), 2011)
Chronic hepatosplenomegaly, which is known to have a complex aetiology, is common amongst children who reside in rural areas of sub-Saharan Africa. Two of the more common infectious agents of hepatosplenomegaly amongst these children are malarial infections and schistosomiasis. The historical view of hepatosplenomegaly associated with schistosomiasis is that it is caused by gross periportal fibrosis and resulting portal hypertension. The introduction of ultrasound examinations into epidemiology studies, used in tandem with clinical examination, showed a dissociation within endemic communities between presentation with hepatosplenomegaly and ultrasound periportal fibrosis, while immuno-epidemiological studies indicate that rather than the pro-fibrotic Th2 response that is associated with periportal fibrosis, childhood hepatosplenomegaly without ultrasound-detectable fibrosis is associated with a pro-inflammatory response. Correlative analysis has shown that the pro-inflammatory response is also associated with chronic exposure to malarial infections and there is evidence of exacerbation of hepatosplenomegaly when co-exposure to malaria and schistosomiasis occurs. The common presentation with childhood hepatosplenomegaly in rural communities means that it is an important example of a multi-factorial disease and its association with severe and subtle morbidities underlies the need for well-designed public health strategies for tackling common infectious diseases in tandem rather than in isolation.